The sensory qualities of stored mango juice packed in different types of coated tin containers - Mamburam, Nerissa R.; Acevedo, Teresita P. (1978.)
Samples of mango juice produced by the UP Pilot Food Plant were taken to determine the relation between the can types and some physico-chemical properties and sensory properties of the product. Mango juices store for 4 and 6 months were packed in C-enamel can, products stored for 0 and 7 months in Oleo-resin coated can (ORC) and mango juice packed in plain tin can body with C-enameled can ends stored for 6 months were compared. For the physico-chemical properties, tin content determination using the method recommended by Cameron and Brittain (i.e. making use of the Atomic Absorption Spectrophometer); % Titratable Acidity; soluble solids (°Bx) content and general appearance of the can were determined. Twenty panelists trained the metallic or tinny flavor in the juice evaluated the product according to its color. metallic taste, metallic odor, presence of metallic particles, consistency and general acceptability. Results showed that there was no relation between the can types and the soluble solids content. Products stored for 6 months and packed in plain tin can body had low % titratable acidity and highest amount of tin (45 ppm). However, the panelists observed that it had the least metallic taste with the other four samples. A C-enameled product stored for four months had the highest mean score of 4.1 for metallic taste. It contained 30 ppm tin but had a relatively high % TA of 0.50. The results of the study also showed that the C-enamel packed product stored for 8 months, ORC packed juice stored for 7 months and the product stored for 6 months in plain tin can did not have significant difference in acceptability. These three products were equally preferred having mean scores corresponding to like slightly
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Canned mango juice; Tin -- Analysis